Autoclaving of the middle ear ossicles in an animal experimental model. (December 2013) - Skoloudik, Lukas; Kalfert, David; Zborayova, Katarina; Laco, Jan
Abstract Conclusion: Autoclaving the ossicles for 4 min at 134°C impacts superficial devitalization and elimination of the squamous epithelium on the surface of the ossicles. Bone maintains the integrity, firmness, and lamellar structure and ossicles are integrated into the middle ear without any adverse reactions. Objective: Sixteen guinea pigs were used to explore the effect of autoclaving on middle ear ossicles. Methods: Harvested incudomallear complex was autoclaved for 4 min at 134°C and implanted back into the middle ear cavity. Exploration of the middle ear was carried out 30 days after implantation. Results were compared with a control group of 16 non-autoclaved ossicles. Results: Autoclaved ossicles maintained their integrity, firmness, shape, and lamellar structure with Haversian systems. Autoclaving substantially decreased the vitality of the ossicles. The middle ear mucosa overgrew on the ossicular surface. No adverse reactions of soft tissue against ossicles occurred. Although the autoclaved ossicles were implanted with tympanic membrane (squamous epithelium) the histological examination did not demonstrate any residuum of squamous epithelium. In the control group we proved the presence of squamous epithelium on the manubrium surface in all cases; all ossicles were vital without signs of ostitis.